IMPLEMENTASI METODE PEMBELAJARAN BERBASIS PROYEK DALAM MATA KULIAH KEWIRAUSAHAAN UNTUK MENINGKATKAN KEMAMPUAN BISNIS MAHASISWA INSTITUT AGAMA ISLAM TASIKMALAYA - Nurnawati, Rani (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to explore the effectiveness of project-based learning (PBL) method in improving students' business skills in Entrepreneurship course at Tasikmalaya Islamic Institute. The research method used is a qualitative approach with a case study method, which involves in-depth interviews, participatory observation, and document analysis. The results showed that PBL contributed to improving students' managerial skills, critical thinking ability, and creativity in facing business challenges. In addition, students involved in real projects showed higher levels of self-confidence and had more innovative and independent entrepreneurial characters. However, the implementation of this method still faces obstacles such as limited resources and students' lack of experience in running a business. Therefore, support from educational institutions in the form of mentoring and business facilities is needed to increase the effectiveness of this method. Thus, PBL can be an effective learning strategy in teaching entrepreneurship in faith-based universities